Wrocławski eksperyment handlu dobrami trwałego użytku - Michalski, Eugeniusz (Wydział Prawa i Administracji UAM, 1969)
In the organizational structure of home trade in Poland the sale of goods of permanent consumption has belonged to specialized and non-specialized enterprises so far. In the result of some organizational changes in Wrocław trade the specialized enterprises have taken over the retail trade from MHD enterprises, located in the territory of Wrocław and the voivodeship of Wrocław. This reorganization exerted considerable influence on forming the size of sale and supplies. The assortment of goods was reduced but at the same time the amount of articles offered for sale increased. After the reorganization the trade enterprises are interested in starting retail cooperative workshops close to their own shops. The shops are now supplied according to a distribution list coordinated with the shop managers. The initiative of shop managers has been reduced to analyzing the demand and applying for the demanded articles that are new in the market.
Wroclaw Experiment in the Trade of Goods of Permanent Consumption